Effect of implicit perceptual-motor training on decision-making skills and underpinning gaze behavior in combat athletes - Milazzo, N.; Farrow, D.; Fournier, J. F. (Perceptual and Motor Skills, 2016)
This study investigated the effect of a 12-session, implicit perceptual-motor training program on decision-making skills and visual search behavior of highly skilled junior female karate fighters (M age = 15.7 years, SD= 1.2). Eighteen participants were required to make (physical or verbal) reaction decisions to various attacks within different fighting scenarios. Fighters' performance and eye movements were assessed before and after the intervention, and during acquisition through the use of video-based and on-mat decision-making tests. The video-based test revealed that following training, only the implicit perceptual-motor group (n = 6) improved their decision-making accuracy significantly compared to a matched motor training (placebo, n = 6) group and a control group (n = 6). Further, the implicit training group significantly changed their visual search behavior by focusing on fewer locations for longer durations. In addition, the session-by-session analysis showed no significant improvement in decision accuracy between training session 1 and all the other sessions, except the last one. Coaches should devote more practice time to implicit learning approaches during perceptual-motor training program to achieve significant decision-making improvements and more efficient visual search strategy with elite athletes. ABSTRACT FROM AUTHOR